Associations between vitamin A and K intake and lung function in the general US population: evidence from NHANES 2007–2012 - Chen, Yi-Chuan; Hung, Ming-Szu (Frontiers in Nutrition, 2024)
While nutrition's critical role in enhancing respiratory health is acknowledged, the specific impacts of vitamins A and K on lung function remain largely unexplored. The study aimed to evaluate the relationships between vitamins A and K intake and lung function. The cross-sectional study focused on adults aged 20-79 with utilizing data from US National Health and Nutrition Examination Survey (NHANES) 2007-2012. Lung function was assessed by measuring forced expiratory volume (FEV1), forced vital capacity (FVC), and the ratio of these two values (FEV1/FVC). Regression model was performed to determine the associations between intake of vitamins A and K and outcomes. Data of 10,034 participants (representing 142,965,892 adults in the US) were analyzed. After adjusting for relevant confounders, multivariable analysis revealed one μg/day increase of vitamin A intake was significantly associated with 0.03 ml increased FEV1 (p=0.004) and 0.04 ml increased FVC (p<0.001). In addition, one μg/day increase in vitamin K intake was significantly associated with 0.11 ml increased FEV1 (p=0.022). Neither vitamin A and K intake was associated with FEV1/FVC or presence of airway obstruction. In conclusions, in relatively healthy population of the US, greater vitamin A or K intake was independently associated with better lung function assessed by spirometry. Benefits of such vitamins for pulmonary health should be confirmed in future randomized controlled trials.